Rainfall shocks and crop productivity in Zambia: implication for agricultural water risk management - Matchaya, Greenwell C.; Tadesse, G.; Kuteya, A. N. (Elsevier, 2022)
This paper investigates the impact of erratic rainfall and related water problems on agricultural productivity. The paper also aims to shed light on the conceptual importance of understanding the incidence and impacts of rainfall shocks for choosing feasible agricultural water risk management strategies both at household and policy levels. To achieve these goals we develop a conceptual framework, use national representative data from Zambia’s crop estimates survey for 2017/2018 farming season, employ fixed effects regression approach, and find that dry spells, excessive floods, incidence of water logging are all detrimental to crop productivity. The crop-based equations also reveal the differential impacts of the rainfall shocks on different crops. Since the effect of water factors including dry spells, floods and water logging on agricultural productivity is dependent on the crop types, it is important for the Zambian government as well as other countries to take this into account when planning and implementing strategies for agricultural water risk management.